Enhancing reef fish diversity using artificial reef-building: A case study of coral reef rehabilitation on Nyamuk Island, Anambas Islands. Issue 1 (December 2021) - Prabowo, B; Rikardi, N; Setiawan, M A; Santoso, P; Yonvitner,; Arafat, D; Subhan, B; Afandy, A
Abstract: CCMRS-IPB conducted coral reef rehabilitation at damaged coral reefs around Nyamuk Island. Those artificial reef buildings for rehabilitation gave shelter spaces for reef fish. This research aims to calculate the effect of coral reef-building, which enhances rugosity to the reef fish diversity around the rehabilitation sites. The study was conducted on Nyamuk Island in the Anambas Islands. Reef fish were sampled annually from 2014 to 2019 using the underwater visual census. The Diversity index and non-Metric Multidimensional Scaling were built to discover reef fish diversity, and reef fish species were affected the most. Yearly data shows an escalation number of reef fish abundance and richness at the end of 2019. The major reef fish group is found to have constant diversity throughout the year compared to other functional groups. The target reef fish group came to this rehabilitation ecosystem primarily attracted by nourishment availability. There is a shift in the reef fish diversity from the early year to the project end. Generally, major reef fish groups will be refuged first around the rehabilitation sites, especially territorial types. Target fish groups from herbivorous and carnivorous types will mostly come along after their food availability and location to get around.